Effect of Silicon Addition on High-Temperature Solid Particle Erosion-Wear Behaviour of Mullite-SiC Composite Refractories Prepared by Nitriding Reactive - Xiaochao Li; Shusen Chen; Zhaohui Huang; Minghao Fang; Yan’gai Liu; Xiaowen Wu; Juntong Huang; Baolin Liu (Advances in Materials Science and Engineering)
Solid particle erosion-wear experiments on as-prepared mullite-SiC composite refractories by nitriding reactive sintering were performed at elevated temperatures, using sharp black SiC abrasive particles at an impact speed of 50 m/s and the impact angle of 90° in the air atmosphere. The effects of silicon powder addition and erosion temperature on the erosion-wear resistance of mullite-SiC composite refractories were studied. The test results reveal that Si powders caused nitriding reaction to form β-sialon whiskers in the matrix of mullite-SiC composite refractories. The erosion-wear resistance of mullite-SiC composite refractories was improved with the increase of silicon powder addition and erosion temperature, and the minimum volume erosion rate was under the condition of 12% silicon added and a temperature of 1400°C. The major erosion-wear mechanisms of mullite-SiC composite refractories were brittle erosion at the erosion temperature from room temperature to 1000°C and then plastic deformation from 1200°C to 1400°C.